Electroacupuncture Suppresses the NF-κB Signaling Pathway by Upregulating Cylindromatosis to Alleviate Inflammatory Injury in Cerebral Ischemia/Reperfusion Rats - Jiang, Jin; Luo, Yong; Qin, Wenyi; Ma, Hongmei; Li, Qiongli; Zhan, Jian; Zhang, Ying (Frontiers in Molecular Neuroscience, 2017)
Electroacupuncture (EA) may reduce inflammatory injury by inhibiting nuclear factor-kappa B (NF-κB) signaling pathway activation after ischemic stroke. Thus, we explored temporal and spatial expression of cylindromatosis (CYLD), a negative feedback inhibitor of the NF-κB signaling pathway, to learn whether CYLD is essential for EA and reduction of inflammatory injury after focal cerebral ischemia/reperfusion. A middle cerebral artery occlusion/reperfusion (MCAO/R) model was established in male Sprague-Dawley (SD) rats and CYLD gene interference was used to investigate a potential role of neuroprotection. Rats were treated with EA (1 mA, 20 Hz for 5 min, 2 Hz for 30 min) at Baihui (GV 20), Hegu (LI 4), and Taichong (LR 3) acupoints, once daily, beginning 2 h after focal cerebral ischemia. Microglial activation and co-expression of CYLD and NF-κB were measured with immunofluorescence. Neuronal CX3CL1 expression was assayed to investigate the role of EA in the interaction between neurons and microglia via upregulation of CYLD. Then, CYLD, NF-κB p65 and p-IκBα protein expression was measured with Western blot. CYLD was mainly expressed in neurons of the peri-ischemic area after MCAO/R in rats and EA upregulated CYLD mRNA and protein from 24 to 72 h after focal cerebral ischemia/reperfusion. In addition, CYLD overexpression was positively correlated to neurobehavior and negatively connected with infarct volume and pro-inflammatory cytokines (TNF-α and IL-1β). Upregulation of CYLD by EA prevented NF-κB nuclear translocation and inhibition of neuronal CX3CL1 expression, which repressed activation of microglia. Finally, CYLD silencing significantly weakened suppression of the NF-κB signaling pathway by EA. In conclusion, upregulation of CYLD may underlie how EA could alleviate inflammatory injury after focal cerebral ischemia/reperfusion.